Embrionary way to create a fatty liver in portal hypertension - Aller, Maria-Angeles (World J Gastrointest Pathophysiol, 2017)
Portal hypertension in the rat by triple partial portal vein ligation produces an array of splanchnic and systemic disorders, including hepatic steatosis. In the current review these alterations are considered components of a systemic inflammatory response that would develop through three overlapping phenotypes: The neurogenic, the immune and the endocrine. These three inflammatory phenotypes could resemble the functions expressed during embryonic development of mammals. In turn, the inflammatory phenotypes would be represented in the embryo by two functional axes, that is, a coelomic-amniotic axis and a trophoblastic yolk-sac or vitelline axis. In this sense, the inflammatory response developed after triple partial portal vein ligation in the rat would integrate both functional embryonic axes on the liver interstitial space of Disse. If so, this fact would favor the successive development of steatosis, steatohepatitis and fibrosis. Firstly, these recapitulated embryonic functions would produce the evolution of liver steatosis. In this way, this fat liver could represent a yolk-sac-like in portal hypertensive rats. After that, the systemic recapitulation of these embryonic functions in experimental prehepatic portal hypertension would consequently induce a gastrulation-like response in which a hepatic wound healing reaction or fibrosis occur. In conclusion, studying the mechanisms involved in embryonic development could provide key results for a better understanding of the nonalcoholic fatty liver disease etiopathogeny.